Network analysis of depressive symptomatology in underweight and obese adults - Ramos Vera, Cristian (2022)
Background: Depressive symptoms can affect people’s quality of life and social environment. In addition, in severe situations, they can lead to suicidal behaviors. Objective: This study aimed to analyze the differences in depressive symptoms in underweight and obese Peruvian adults. Methods: A cross-sectional study was carried out based on secondary data obtained from the Instituto Nacional de Estadística e Informática (INEI), Lima, Peru. A sample of 10053 participants was considered, of which 55.96% were women. Two Gaussian plot models were estimated and the levels of depressive symptomatology were compared between the 2 groups (adults with underweight and obese). Results: A total of 1510 (15.02%) were underweight adults and 8543 (84.98%) were obese adults. There were differences in the reporting of depressive symptoms in the underweight group; the most central items were “Depressed mood” (PH2), “Tiredness/ low energy” (PH4), and “Psychomotor difficulties” (PH8). Conclusion: This study provides new evidence on the dynamic relationship between depressive symptoms according to the body mass index categories (underweight and obese) assessed.